2021
DOI: 10.4269/ajtmh.20-1088
|View full text |Cite
|
Sign up to set email alerts
|

Field Efficacy of Larvivorous Fish and Pyriproxyfen Combined with Community Engagement on Dengue Vectors in Cambodia: A Randomized Controlled Trial

Abstract: Evidence on the effectiveness of low-cost, sustainable biological vector control tools for Aedes mosquitoes is limited. Therefore, the purpose of this trial was to estimate the impact of guppy fish in combination with the larvicide pyriproxyfen (PPF) (Sumilarv® 2MR) and communication for behavioral impact (COMBI) activities to reduce entomological indices in Cambodia. In this cluster randomized, controlled superiority trial, 30 clusters comprised of one or more villages each was allocated in a 1:1:1 ratio to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…In the February 2020 survey, guppies were found in 40.7% of eligible containers in the Intervention Arm. This compares with the earlier cluster-randomised trial in the same villages in which guppy coverage was approximately 60–70% [ 17 ] and with non-randomised studies in Cambodia in which Poecilia reticulata were found in 57% of eligible containers [ 20 ] and 88% of eligible containers [ 21 ], respectively. Guppy fish coverage may have been lower in this project than previous projects due to the passive nature of guppy fish distribution, which relied in particular on school children taking fish home to their households.…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…In the February 2020 survey, guppies were found in 40.7% of eligible containers in the Intervention Arm. This compares with the earlier cluster-randomised trial in the same villages in which guppy coverage was approximately 60–70% [ 17 ] and with non-randomised studies in Cambodia in which Poecilia reticulata were found in 57% of eligible containers [ 20 ] and 88% of eligible containers [ 21 ], respectively. Guppy fish coverage may have been lower in this project than previous projects due to the passive nature of guppy fish distribution, which relied in particular on school children taking fish home to their households.…”
Section: Discussionsupporting
confidence: 44%
“…The use of the guppy fish Poecilia reticulata in household water containers was found to be highly acceptable to the households in the surveys, and guppies were present in almost 10% of containers in the August 2018 survey, before the project began to distribute the fish, showing a background use of guppy fish in Kampong Cham province which is likely related to previous studies of guppies in the same province and same villages [ 17 , 21 ]. Guppy fish appeared to be effective predators of immature mosquito stages, although they were unable to eat all the immature stages in their containers: across the four surveys, the Container Index in containers with guppies was 4.0% compared with 21.6% in containers without guppies, an 81% reduction.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations